Quality of the Spermatozoa of the Giant Grouper Epinehelus lanceolatus (Bloch, 1970) after Freezing and the Effect of Egg Yolk as a Natural Cryoprotectant - Abinawanto, . (Advanced Aspects of Engineering Research Vol. 2, 2021)
The grouper Epinephelus lanceolatus is a vulnerable species of high economic value, therefore this study aims to determine the effect of the combination of 6% glycerol with different concentrations of egg yolk on the quality of grouper Epinephelus lanceolatus spermatozoa of post-cryopreservation (Bloch, 1970). A grouper giant semen fish were obtained using the stripping method. The diluent consists of Marine Fish Ringer, 6% glycerol and different concentrations of egg yolk (0%; 5%; 10%; 15%; 20%; and 25%). The equilibration was performed at 4ºC for 10 minutes, and freezing was carried out at (-20ºC) for 48 hours using a freezer, as well as defrosting at 45ºC for 30-60 seconds. The evaluation of semen was carried out macroscopically (color, volume, and pH) and microscopically (motility, viability, and abnormality) as well as the ability to fertilize the tigers grouper eggs. Based on the ANOVA and Tukey test, there was a significant difference (p< 0.05) in motility, viability, and ability to fertilize post-cryopreserved grouper spermatozoa, but there was no significant effect on the maintenance after post-cryopreserved spermatozoa abnormalities (p> 0.05). The results showed that 15% of the egg yolk treatment was the optimum concentration because it produces the highest mean percentage values of motility, viability and the fertilization ability of 83.64 ± 1.72%, 81.44 ± 2.06% and 77.31 ± 1.90%, respectively. The lowest average value correspond with the percentage of abnormalities of 21.50 ± 1.20%.